Crowdsourcing Last Mile Delivery: Strategic Implications and Future Research Directions. Issue 1 (26th December 2017) - Castillo, Vincent E.; Bell, John E.; Rose, William J.; Rodrigues, Alexandre M.
Abstract : The rise of e‐commerce over the past 20 years has created an increased need for responsive omnichannel distribution to meet the last mile challenge. Some companies are experimenting with the use of the sharing economy business model to augment distribution strategies. The use of so‐called "Crowdsourced Logistics" (CSL) is becoming more prevalent in practice, but the role in logistics strategy of this new phenomenon has not been thoroughly investigated and understood. Using a contingency theory lens, this research contributes a nascent understanding of how CSL performs in terms of logistics effectiveness by simulating same‐day delivery services from a distribution center to 1, 000 customer locations throughout New York City under dynamic market conditions and by comparing the results to those of a traditional dedicated fleet of delivery drivers. The findings are analyzed to suggest how firms may find strategic benefit using CSL. An agenda for future research is provided to explore these strategic implications and to deepen knowledge about the CSL phenomenon.